Recognizing child’s lethal defect as a threat as well as progress in values for parents - Jarzębińska, Aneta (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
The focus of this particular work is the analysis of the situation in which the parentsfind themselves after their child has been diagnosed with a lethal abnormality. Specificallyparents with a child who has been diagnosed with a rare aberration of chromosomesknown as the Edward’s Syndrome.
Keywords: family; child; lethal abnormality; terminally ill child; Edward’s Syndrome